LEARNING DESIGN OF EXPONENTIAL NUMBERS THROUGH THE DESIGN OF A HYPOTHETICAL LEARNING TRAJECTORY USING DISCOVERY LEARNING - Muhtadi, Dedi; Yulianto, Eko; Hermanto, Redi; Virawanti, Tiana (Journal of Authentic Research on Mathematics Education (JARME), 2024)
This research aims to develop an effective learning design for understanding the concept of exponentiation by applying the Discovery Learning model using the Hypothetical Learning Trajectory (HLT) as the framework foundation. The research method used is a design research method consisting of three main stages: preliminary design, teaching experiment, and retrospective analysis. The initial stage involves literature analysis and the design of an HLT tailored to the concept of exponentiation. The instructional design is based on the prepared HLT and tested through two experimental stages: pilot experiment and teaching experiment. Retrospective analysis is conducted to compare the initial HLT with the Actual Learning Trajectory (ALT) achieved during the learning process. Data is collected through observation to monitor learning activities and environmental conditions, as well as through recordings of learning activities to gain an understanding of student participation in the design experiments. Additionally, Student Worksheets (SW) are used as aids for students to understand the concept of exponentiation, and evaluation questions are used to measure students' learning outcomes in the subject matter. Interviews are also conducted to gain a deeper understanding from the student's perspective. The results of this research make a significant contribution to the development of more effective mathematics learning methods, particularly in understanding the concept of exponentiation, and provide guidance for teachers to design learning that is more relevant to students' daily lives. The implications of the research results provide guidelines for teachers in designing learning that is more relevant to students' daily lives.